4 - African Feminism and the Recognition of Cohabitation Under Customary Law - Ditsela, Maphoko; Diala, Anthony; Ozoemena, Rita (Africa Development, 2024)
Cohabitation is the co-residence of two persons, as if they are husband and wife, with or without children. The phenomenon, which is becoming increasingly common is, however, not recognised as a valid family form in African customary law. The result is that many Black women in these unofficial relationships are without legal protection, particularly with respect to property rights and the rights to equality, human dignity and freedom. This article argues that the concept of African feminism presents possibilities for policy-makers to bridge the gap between women’s rights and the prescripts of tradition. Furthermore, it offers solutions for closing gaps in the law that have been created by contentious issues in the legal requirements for a valid marriage, such as payment of bride wealth and the waiver of some marriage rites.